2023
DOI: 10.1097/tp.0000000000004489
|View full text |Cite
|
Sign up to set email alerts
|

Higher Fasting Pretransplant C-peptide Levels in Type 2 Diabetics Undergoing Simultaneous Pancreas-kidney Transplantation Are Associated With Posttransplant Pancreatic Graft Dysfunction

Abstract: Background. Among selected patients with type 2 diabetes mellitus (T2DM), simultaneous pancreas and kidney (SPK) transplants can be an effective option. However, data are limited about outcomes in T2DM SPK recipients based on the pretransplant C-peptide levels. Methods. In this study, we reviewed all T2DM SPK recipients and categorized them based on the pretransplant fasting C-peptide levels into 3 groups: low (≤2 ng/mL), medium (>2–8 ng/mL), and high (>8 ng/mL). Several measures of graft failures (GFs), gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…For instance, recent evidence suggests that higher pre-transplant fasting serum C-peptide levels are associated with an increased risk of graft failure or dysfunction. 31,32…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, recent evidence suggests that higher pre-transplant fasting serum C-peptide levels are associated with an increased risk of graft failure or dysfunction. 31,32…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the routine use of biomarkers that can predict post‐transplant outcomes in SPTK may be beneficial. For instance, recent evidence suggests that higher pre‐transplant fasting serum C‐peptide levels are associated with an increased risk of graft failure or dysfunction 31,32 …”
Section: Discussionmentioning
confidence: 99%
“…We read with interest the report by Parajuli et al 1 , chronicling the University of Wisconsin experience in simultaneous pancreas-kidney transplantation (SPKT) according to the pretransplant fasting serum C-peptide levels. The authors demonstrated that higher pretransplant C-peptide levels predicted the risk of a composite outcome (combination of pancreas graft failure according to the United Network for Organ Sharing definition and pancreas graft dysfunction defined as initiation of any antidiabetic agent) posttransplant in patients with a type 2 diabetes phenotype.…”
mentioning
confidence: 99%
“…The authors demonstrated that higher pretransplant C-peptide levels predicted the risk of a composite outcome (combination of pancreas graft failure according to the United Network for Organ Sharing definition and pancreas graft dysfunction defined as initiation of any antidiabetic agent) posttransplant in patients with a type 2 diabetes phenotype. 1,2 Recipients were categorized into 3 groups based on pretransplant fasting serum C-peptide levels: low (≤2 ng/mL, n = 14), medium (>2–8 ng/mL, n = 47), and high (>8 ng/mL, n = 15). The uncensored composite outcome of pancreas graft failure or dysfunction occurred in 0% in the low, 23% in the medium, and 33% of patients in the high C-peptide groups, respectively, suggesting that higher levels of pretransplant C-peptide are associated with inferior posttransplant outcomes.…”
mentioning
confidence: 99%
“…In this edition of Transplantation , Parajuli et al at the University of Wisconsin present new details, which should help improve pretransplant education for patients and help inform providers with posttransplant management. 6 This group and their predecessors have a storied historical experience with pancreas transplantation, including their informative manuscript of 1000 SPKs, 7 and more recently, their well-regarded report of SPK comparing type 1 diabetes mellitus (T1DM) and T2DM recipients. 8 Pham et al found evidence suggesting less restricted selection criteria for SPK in T2DM patients was possible, as compared with T1DM recipients, as well as similar rates of freedom from posttransplant diabetes and graft survival at 5 y.…”
mentioning
confidence: 99%